Exploiting mesoporous silica, silver and gold nanoparticles for neurodegenerative diseases treatment - Ribeiro, Taís C. [UNESP]; Sábio, Rafael M. [UNESP]; Carvalho, Gabriela C. [UNESP]; Fonseca-Santos, Bruno; Chorilli, Marlus [UNESP] (Elsevier, 2022)
Neurodegenerative diseases (NDs) are considered public health problem characterized by neural loss causing cognitive and behavioral impairments. It is currently possible to use drugs capable of controlling the symptoms caused by these diseases. However, treatment is not able to prevent neural loss. In addition, poor solubility, low bioavailability due to the inability for crossing the blood–brain barrier (BBB) are described as the main limitations of the treatment. Nanotechnology involves the development of nanoscale drug delivery systems and they have been employed to optimize therapeutics face to several diseases treatment. In light of this, this review describes the highlights on the fabrication of nanotechnology-based drug delivery systems emphasizing mesoporous silica, gold and silver nanoparticles (MSNs, AuNPs and AgNPs, respectively) and their biological behavior for the treatment of Alzheimer's and Parkinson diseases (ADs and PDs, respectively).
Keywords: Drug delivery systems; Mesoporous silica nanoparticles; Neurodegenerative diseases treatment; Silver and gold nanoparticles; Smart nanocarriers